Analyzing the impact of human development, price stability, and Islamic social funds on Indonesia’s economic growth - Mardiatunnisa Mardiatunnisa (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: This study aims to analyze the factors that influence Indonesia’s economic growth, focusing on the impact of the Human Development Index (HDI), inflation, and Islamic social funds, which include zakat, infaq, and sadaqah (ZIS), during the period 2003-2024. This study was motivated by the slowdown in Indonesia’s economic growth, which only reached 5.27% in the 2022-2024 period. In addition, previous studies that have shown uncertainty in the relationship between HDI, inflation, and ZIS on economic growth necessitate a more comprehensive and long-term analysis. Methods: This study uses secondary data obtained from official reports from the Central Bureau of Statistics of Indonesia/Badan Pusat Statistik Indonesia, Indonesian Bank/Bank Indonesia (BI), and the National Zakat Collection Agency/Badan Amil Zakat Nasional (BAZNAS). Data analysis was performed using multiple linear regression with the Ordinary Least Squares (OLS) approach, processed with EViews 12 software, to test the effect of independent variables on economic growth. Findings: The results indicate that HDI and ZIS have a positive and significant impact on economic growth, with coefficients of 3.089 and 0.0401, respectively. In contrast, inflation has no significant effect on economic growth. These findings support the theory that improving the quality of human development and optimizing the management of Islamic social funds can promote inclusive economic growth. Simultaneously, the variables of HDI, inflation, and ZIS were found to have a significant effect on economic growth, with the model explaining 89% of the variation. Conclusion: Improving the quality of human resources and optimizing the collection of Islamic social funds have been proven to increase Indonesia’s economic growth. Novelty/Originality of this article: The novelty of this study lies in the integration of the Human Development Index, inflation, and Islamic social funds (zakat, infaq, and sadaqah) variables into a single long-term analysis model. The study offers more representative and robust empirical evidence on the determinants of economic growth in Indonesia.